Pose Calibration for 2D Laser Profiler Integrated in Five-Axis Machine Tools. Issue 1 (April 2020) - Zhang, S; Duan, X; Zeng, C; Shi, K; Zhang, X; Bi, Q; Wang, Y
Abstract: Laser scanning is a fast and effective method to acquire the 3D surface profiles of part. To implement on-machine measurement (OMM), the 2D laser profiler could be integrated in five-axis machine tools and moves under the command of the computer numerical control (CNC) system. The 2D profile data and the corresponding machine coordinates are acquired and saved by the CNC system, and then converted to 3D point cloud using the kinematic model. Therefore, calibration of the position and orientation of the laser profiler with respect to the machine tool will directly influence the inspection accuracy. In this paper, a pose calibration method is proposed to identify the position and orientation of the laser sensor. A laser scanning system integrated in five-axis machine tool is developed. The position and orientation deviations between the local laser coordinate system (LCS) and tool coordinate system (TCS) are defined. Then, a designed calibration block is scanned, and its feature is reconstructed. Furthermore, the position and orientation of the laser profiler is identified by comparing the reconstructed features with the designed features. Finally, the position and orientation deviations parallel to five axes of the machine tool are compensated by coordinate offset, and the remaining orientation deviation is corrected by the kinematic model during converting measurement data to 3D point cloud. Experiment is carried out to validate the proposed method.